Escape Room, a New Method to Assess the Learning of Nursing Students: A Scoping Review - Mahin Naderi far; Fateme Rezaei Kahkhaei; Mohammad Hosein Abdollahi Nodehi (Strides in Development of Medical Education)
Background: The escape room game is a very useful and effective learning process used to teach various medical students, including nursing students. Escape rooms are increasingly used in higher education to supplement traditional teaching methods, allowing students to recall and apply knowledge gained in the classroom. In addition, given that the escape room is fun, it encourages them to study.Objectives: This systematic review aims to investigate the impact of using escape rooms in nursing education and their effectiveness in evaluating students' competencies.Methods: This scoping review adhered to the PICO systematic review guidelines. The present study is a targeted and integrated review. First, a comprehensive search was conducted using keywords related to "escape room", "nursing education", "assessment", "evaluation" and "student learning" in Elsevier, SID, Magiran, Google Scholar, Science Direct, and PubMed databases to identify relevant studies published between 2010 and 2024. The studies about the effect of escape rooms on the teaching and learning of nursing students were included.Results: The first search identified 150 articles. After a more detailed review based on the purpose of the current research, 35 articles were included in the second phase of the study. Finally, after reviewing the full text, 10 articles reported the use. These articles' findings have shown that using escape rooms in nursing education improves student participation, teamwork, effective communication, and problem-solving skills. By carefully designing and implementing escape room activities, nursing educators can increase student engagement, teamwork, critical thinking, and problem-solving skills in a fun and interactive way.Conclusion: This review provides valuable insights into the benefits and potential challenges of incorporating escape rooms into nursing curricula. The immediate feedback and other advantages make escape room training a valuable addition to nursing education. However, it's important to note that more research is needed to fully establish the validity and reliability of using escape rooms as an assessment tool in nursing education.